The expression that correctly shows the sum of opposite numbers is:
\[ (-25) + 25 = 0 \]
This is because the opposite of \(-25\) is \(25\), and when you add them together, the result is \(0\).
Responses
(−25)+25=0
left parenthesis negative 25 right parenthesis plus 25 equals 0
(−25)+(−25)=0
left parenthesis negative 25 right parenthesis plus left parenthesis negative 25 right parenthesis equals 0
(−25)+(−25)=−50
left parenthesis negative 25 right parenthesis plus left parenthesis negative 25 right parenthesis equals negative 50
(−25)+25=50
left parenthesis negative 25 right parenthesis plus 25 equals 50
1 answer
The expression that correctly shows the sum of opposite numbers is:
\[ (-25) + 25 = 0 \]
This is because the opposite of \(-25\) is \(25\), and when you add them together, the result is \(0\).